2019
DOI: 10.1111/nph.15649
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of flattened unifacial leaves in Juncus prismatocarpus (Juncaceae)

Abstract: Summary To reveal the mode of morphogenesis of flattened unifacial leaves, we analysed the cell division direction and distribution on the leaf blade of Juncus prismatocarpus. Using the pulse–chase 5‐ethynyl‐2′‐deoxyuridine method, we quantified and mapped the cell division direction on the leaf blade of J. prismatocarpus and compared the distribution of thickening cell divisions with the expression pattern of DROOPING LEAF (DL), a key gene involved in leaf blade thickening. Thickening cell divisions were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Consistently, PRS is detected in the flattened leaf margin while not in the cylindrical leaf margin (Yamaguchi et al, 2010). Further analysis on cell division direction revealed that there is more thickening cell division on the adaxial domain than on the abaxial domain, which gives rise to flattened leaves like bifacial leaves (Yin and Tsukaya, 2019). Further investigation on unifacial leaf development may provide new insight into how leaves are flattened.…”
Section: Future Perspectivesmentioning
confidence: 78%
“…Consistently, PRS is detected in the flattened leaf margin while not in the cylindrical leaf margin (Yamaguchi et al, 2010). Further analysis on cell division direction revealed that there is more thickening cell division on the adaxial domain than on the abaxial domain, which gives rise to flattened leaves like bifacial leaves (Yin and Tsukaya, 2019). Further investigation on unifacial leaf development may provide new insight into how leaves are flattened.…”
Section: Future Perspectivesmentioning
confidence: 78%
“…Notably, wox3 triple mutant leaves with missing ligules retain adaxial–abaxial patterning at the BSB, indicating that disruption of ligule development is not due to the loss of adaxial–abaxial polarity (Extended Data Fig. 7b,c ) 29 .
Fig.
…”
Section: Resultsmentioning
confidence: 98%
“…Cell pairs suitable for cell division orientation analysis are easily recognized in both Arabidopsis (Figure 3A) and J. prismatocarpus (Figure 3B) Tsukaya, 2016 and2019). Using these cell pairs, cell division angles can be quantified (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, we showed that cell division orientation is locally non-stochastic in leaf primordia of Arabidopsis thaliana (Arabidopsis), a model plant species for which leaf morphogenesis has been extensively studied (Yin and Tsukaya, 2016). Furthermore, we combined this method with conventional paraffin sectioning and analyzed cell division orientation in leaves with more complex structures such as those of Juncus prismatocarpus, a non-model plant species (Yin and Tsukaya, 2019).…”
mentioning
confidence: 99%